Operative Outcomes after Open Abdominal Wall Reconstruction with Retromuscular Mesh Fixation Using Fibrin Glue versus Transfascial Sutures. Issue 9 (September 2017) - Weltz, Adam S.; Sibia, Udai S.; Zahiri, H. Reza; Schoeneborn, Alexa; Park, Adrian; Belyansky, Igor
Ideal fixation techniques have not been fully elucidated at the time of complex open abdominal wall reconstruction (AWR). We compared operative outcomes and quality of life with retromuscular mesh fixation using fibrin glue (FG) versus transfascial sutures (TS). Retrospective review identified complex hernia patients who underwent open AWR with mesh from November 2012 through April 2016. Multivariate analysis examined postoperative outcomes between groups. Quality of life was assessed using the Carolinas Comfort Scale. Seventy-five patients (18 FG vs 57 TS) with mean age (54.3 vs 53.9 years, P = 0.914), body mass index (35.8 vs 34.7 kg/m 2, P = 0.623) and American Society of Anesthesiologist score (2.6 vs 2.5, P = 0.617) were reviewed. No differences in wound (P = 0.072) and nonwound (P = 0.639) related complications were noted between groups. Risk of reoperations (P = 0.275) and 30-day readmissions (P = 0.137) were also comparable. The TS group was twelve times more likely to report pain at six-month follow-up compared with FG (12.29 OR, 95 per cent confidence interval 1.26–120.35, P = 0.031). No hernia recurrences were noted in either group at a mean follow-up of 390 ± 330 days. The use of FG to secure mesh in the retromuscular space during complex open AWR may be a safe alternative to penetrating transfascial fixation with potential to reduce chronic pain.